Studies on the Degradation of Human Fibrinogen by Plasmin and Trypsin - Beck, E. A; Jackson, D. P (Thrombosis and Haemostasis, 1966)
The effects of trypsin and plasmin on the functional and physicochemical properties of purified human fibrinogen were observed at various stages of proteolysis. Concentrations of plasmin and trypsin that produced fibrinogenolysis at comparable rates as measured in a pH stat produced, at similar rates, loss of precipitability of fibrinogen by heat and ammonium sulphate and alterations in electrophoretic mobility on starch gel. Trypsin produced a more rapid loss of clottability of fibrinogen and a more rapid appearance of inhibitors of the thrombin-fibrinogen clotting system than did plasmin. Consistent differences were noted between the effects of trypsin and plasmin on the immunoelectrophoretic properties of fibrinogen during the early stages of proteolysis.These results are consistent with the hypothesis that trypsin initially reacts with the same peptide bonds of fibrinogen that are split by thrombin, but these same bonds do not appear to be split initially by plasmin. Measurement of the various functional and physico-chemical changes produced by the action of trypsin and plasmin on fibrinogen can be used to recognize various stages of proteolysis.